幼教人員對女性主管行政領導認知態度之調查研究 The Survey Study of Early Childhood Educators' Cognitive Attitudes Towards the Administrational Leadership of Female Managers - 陳儒晰 Ru-Si Chen; 邱方晞 Fang-Hsi Chiu (National Taiwan Normal University, 2010)
本研究以臺北地區幼教人員為研究對象進行問卷調查，探討其對於女性主管在幼教行政領導實務中的思考及認知態度。研究者自編「女性主管行政領導認知態度量表」問卷，涵蓋「社會結構」、「弱勢地位」、「個人特質」、「積極參與」與「表現優勢」等層面，運用結構方程模式探討幼教人員對此議題之想法。統計結果顯示，問卷的假設因素構念之測量模式檢定具有良好適配，且路徑關係的結構模式分析證明研究假設之成立。研究發現，幼教人員認為社會結構因素影響女性主管的弱勢地位、積極參與和表現優勢等態度，且指出個人特質及積極參與態度亦會影響女性主管之表現優勢，社會結構與個人特質構念則呈現負相關。最後，研究者針對研究發現進行討論並提出未來研究之參考。 This study explored the early childhood educators' attitudes toward administrational leadership in Taipei area by questionnaire. An Attitude Scales toward Administrational Leadership of Female Managers Survey was developed. The questionnaire consisted of five factors, including social structure, minority status, personal traits, affirmative engagement, and superior performance, employing structural equation modeling to analyze the data. According to the results, this measurement model indicated the good quality of confirmatory factory analysis, and the path analysis confirmed the study hypotheses. The results indicated that early childhood educators considered the social gender structural factors influence female managers' minority status, affirmative engagement, and superior performance. Their attitudes toward personal traits and affirmative engagement could influence female managers' performance, and there was the negative effect between the construct of social structure and personal traits. The follow-up discussions also conducted and the implications derived form this study was presented.